Transarterial chemoembolization versus surgery/radiofrequency ablation for recurrent hepatocellular carcinoma with or without microvascular invasion. Issue 5 (May 2014) - Jin, Young‐Joo; Lee, Jin‐Woo; Lee, Oh Hyun; Chung, Hyun Jung; Kim, Young Soo; Lee, Jung Il; Cho, Soon Gu; Jeon, Yong Sun; Lee, Kun Young; Ahn, Seung‐Ik; Shin, Woo Young
Abstract Background/Aims Microvascular invasion (MVI) is a well‐known prognostic factor of postoperative recurrence and of overall survival (OS) in patients with hepatocellular carcinoma (HCC). We compared the treatment outcomes of transarterial chemoembolization (TACE) and surgery/radiofrequency ablation (RFA) according to the presence of MVI in patients with early or late recurrent HCC that presented as Barcelona Clinical Liver Cancer (BCLC) stage 0 or A after curative resection for HCC. Methods A consecutive 68 patients with recurrent HCC of BCLC stage 0 or A at our institution between 1998 and 2012 were retrospectively enrolled. We compared the outcomes of patients treated by TACE or surgery/RFA. Tumor recurrence after curative resection was classified as early (≤ 12 months) or late (> 12 months) recurrence. Results Median tumor size was 1.5 cm (range, 1–10 cm), and 67 (98.5%) had HCCs within the Milan criteria. Median post‐retreatment follow‐up duration was 27 months (range, 1–109 months). Of the 68 patients, 19 (27.9%) underwent surgery/RFA, 47 (69.1%) TACE, and 2 (2.9%) were lost to follow‐up. After retreatment, TACE showed significantly higher OS and recurrence‐free survival rates than surgery/RFA in MVI‐positive patients (P = 0.03 and P = 0.05, respectively), but not in MVI‐negative patients (P = 0.95 and P = 0.98, respectively). In particular, in early recurred MVI‐positive patients, TACE had a significantly higher OS rate than surgery/RFA (P = 0.01). Conclusions TACE may be the more effective treatment option for recurrent HCC of BCLC stage 0 or A than surgery/RFA in MVI‐positive patients, especially in those that recur early after curative resection.